2014
DOI: 10.3174/ajnr.a4148
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Blood Flow Pulsatility along the Atlas Slope: A Physiologic Property of the Distal Vertebral Artery?

Abstract: BACKGROUND AND PURPOSE:Physiologic and pathologic arterial tortuosity may attenuate blood flow pulsatility. The aim of this prospective study was to assess a potential effect of the curved V3 segment (Atlas slope) of the vertebral artery on arterial flow pulsatility. The pulsatility index and resistance index were used to assess blood flow pulsatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Recent studies found that pulsatile flow is affected by physiological and pathological vascular geometry when investigating in a proximal-distal approach. 13,30,31 An important finding in this study was that the pulsatile flow that reaches distal arterial segments was augmented with age. Firstly, the PIs in large proximal arteries were increased in elderly (Table 2) and secondly the dampening capacity of the cerebral arteries was more efficient in the young group for all cerebral arterial segments (Table 3).…”
Section: Dampening Of Pulsatile Flow In the Cerebral Arteriesmentioning
confidence: 74%
See 1 more Smart Citation
“…Recent studies found that pulsatile flow is affected by physiological and pathological vascular geometry when investigating in a proximal-distal approach. 13,30,31 An important finding in this study was that the pulsatile flow that reaches distal arterial segments was augmented with age. Firstly, the PIs in large proximal arteries were increased in elderly (Table 2) and secondly the dampening capacity of the cerebral arteries was more efficient in the young group for all cerebral arterial segments (Table 3).…”
Section: Dampening Of Pulsatile Flow In the Cerebral Arteriesmentioning
confidence: 74%
“…10 Flow pulsations in cerebral arteries can be investigated using Doppler ultrasonography and phase-contrast magnetic resonance imaging (PCMRI). [11][12][13] Although Doppler is widely available, it has several drawbacks. The most important is that investigations are limited to the proximal branches of the cerebral arterial tree.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] This characteristic of the brain is underlined by the finding that the large conducting arteries seem to have specific properties to decrease arterial pulsatility to the brain along their course. [17][18][19] It has been suggested in recent work that reduction in vascular elasticity and expansive and contractile forces change the amplitude and length of the arterial pulse and may affect the perivascular clearance of interstitial fluid, diminishing the physiologic transport of metabolites out of the brain including beta-amyloid (Ab). 8,[20][21][22][23][24] Consequently, there is interest in non-invasive methods to assess cerebrovascular hemodynamics as potential systemic pathogenic or exacerbating factors in AD and potential avenues for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of aqueductal CSF stroke volume as a diagnostic marker of ICP alteration is still debated. For the vascular system, pulsatility or resistance indexes of cerebral blood flow are used as indirect measures for the biomechanical properties of the vascular tree and blood pressure [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These authors attributed this result to the increasing flow pulsatility with increasing age, as a result of stiffness of the vessels when elastin is replaced by collagen [8]. In recent studies, Schubert et al showed that arterial blood flow pulsatility decreases from the distal to proximal part of the vessels and that this reduced pulsatility increased with the tortuosity of the vessels at the level of the atlas or of the carotid siphon [6,9]. A study by Stoquart-Elsankari et al in healthy young adults showed that jugular venous flow pulsatility is higher than the superior sagittal sinus flow pulsatility [10].…”
Section: Introductionmentioning
confidence: 99%